Al-Kafa'ah Al-Ihtirafiyyah Li Mudarris Al-Lughah Al-Arabiyah fi Al-Madrasah Al-'Aliyah Al-Hukumiyyah bi Kalimantan Asy-Syarqiyah - Fattah, Mustamin (Dinamika Ilmu, 2020)
This research was conducted to determine the professional competence level of Arabic language teachers who are in Islamic educational institutions, especially in senior high schools (MAN) East Borneo. In addition, other important cases in this study are about teaching Arabic, including strategies to improve the quality of professional teacher competence and Arabic learning. The research design is quantitative descriptive. The population is all of MAN in East Borneo, and the type of sample is cluster random sampling. Data collection techniques are observation, questionnaires, and documentation, while data analysis is a Likert scale and Mean formula to show the general results obtained. The results are based on an assessment of Arabic language skills, evaluation of teaching and learning implementation, professional awareness and teacher performance, and professional consistency that showed the successful of professional competence in Arabic language teachers by using the supported strategies of entire academic community in MAN East Borneo.